1985
DOI: 10.1159/000138133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrafiltration on Peritoneal Dialysis Drug Clearances

Abstract: To determine the effect of dialysate osmolarity on peritoneal dialysis drug transfer, peritoneal dialysis clearances of theophylline, phenobarbital, and tobramycin were determined in 10 rabbits using dialysate containing 1.5 and 4.25% glucose. Urea and creatinine clearances were also obtained for comparison. Under similar dialysis conditions, the peritoneal clearances of the three drugs remained unchanged for the two types of dialysate. In contrast, the peritoneal clearances of urea and creatinine were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The explanation for this is that the capillary membrane permeability of BA was so large that its disappearance from the peritoneal cavity was not significantly affected by the net fluid movement between the capillary bed and the cavity. Lau et al 23 reported that the peritoneal clearances of intravenously injected theophylline, phenobarbital, and tobramycin in rabbits were unchanged for the two types (0.347 and 0.486 osm kg-.') of dialysate, while those of urea and creatinine were significantly higher for the dialysate with the higher tonicity.…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for this is that the capillary membrane permeability of BA was so large that its disappearance from the peritoneal cavity was not significantly affected by the net fluid movement between the capillary bed and the cavity. Lau et al 23 reported that the peritoneal clearances of intravenously injected theophylline, phenobarbital, and tobramycin in rabbits were unchanged for the two types (0.347 and 0.486 osm kg-.') of dialysate, while those of urea and creatinine were significantly higher for the dialysate with the higher tonicity.…”
Section: Discussionmentioning
confidence: 99%